Brachiaria grass for climate resilient and sustainable livestock production in Kenya - Njarui, D.M.G.; Gatheru, M.; Ghimire, Sita R. (Springer, 2020)
Brachiaria grass is a “climate smart” forage that produces high amount of palatable and nutritious biomass for livestock and performs well in infertile soils, sequesters carbon in soil, and provides several environmental benefits. The objective of the study was to validate the productivity of Brachiaria grass and upscale the suitable cultivars for improved livestock feed resources in Kenya. We assume integrating Brachiaria grass into mixed crop-livestock system will enhance feed availability and livestock productivity, leading to increased food and nutrition security. Farmer participatory approach was adopted to evaluate and promote four Brachiaria grass (Brachiaria decumbens cv. Basilisk, B. brizantha cvs. Xaraes, Piata, and MG-4) in the Central Highland and Eastern Midland of Kenya. The extension/advisory approaches used to promote Brachiaria grass cultivars included field days, village knowledge centres, agricultural shows, posters, and linkages with other institutions through multi-actor platform established under the InnovAfrica project. Generally, Brachiaria grass cultivars were more productive than the control (Rhodes grass) in most harvests reaching peak of 5.1–7.7 t/ha in the fifth harvest. For Rhodes grass, DM was less than 4 t/ha in all harvest and died by sixth harvest. Similarly, based on farmers’ evaluation using phenotypic traits, the Brachiaria grass cultivars had higher score than Rhodes grass except cv. Piata. The mean score ranged from 2.75 to 3.19 for Brachiaria cultivars, while for Rhodes the mean score was 2.63. Within 2 years of intervention, over 4000 farmers in the 2 project sites and additional 1500 farmers from other parts of the country have planted the Brachiaria grass. The demand for Brachiaria grass seeds is increasing due to benefits gained, e.g., increased milk production from dairy cattle fed on the grass. Our study will quantify the associated benefits from cultivation of Brachiaria grass with respect to a set of ecological, food and nutrition security, and social-economic indicators.